Alphaherpesvirus‐associated disease in greater bilbies (Macrotis lagotis). Issue 6 (11th May 2016) - Besier, AS; Mahony, TJ; Crockford, M; Gravel, JL; Chapman, TF; O'Dea, MA
Abstract : Case report: A captive breeding colony of 9 greater bilbies ( Macrotis lagotis ) exhibited mild upper respiratory signs and sudden deaths with 100% mortality over a 2‐week period. Histologically, acute necrotising and erosive epithelial lesions throughout the upper respiratory system and bronchi were associated with eosinophilic intranuclear inclusion bodies. Inclusions were also present in hepatocytes and adrenocortical cells, but were not always associated with necrosis. Transmission electron microscopy of lung sections revealed nucleocapsids forming arrays within some nuclei. A pan‐herpesvirus PCR yielded a 440‐bp product, with sequencing confirming homology with the alphaherpesviruses. Viral culture in a marsupial cell line resulted in cytopathic effect consistent with an alphaherpesvirus. Conclusion: This is the first report of a herpesvirus‐associated disease in greater bilbies.